The dechlorination of pentachlorophenol under a sulfate and iron reduction co-occurring anaerobic environment. (September 2017) - Xue, Lili; Feng, Xi; Xu, Yan; Li, Xinfeng; Zhu, Min; Xu, Jianming; He, Yan
Abstract: An anaerobic soil slurry incubation experiment was conducted by controlling different Fe/S mole ratios (1/3, 1/2, 1/1, 2/1, 3/1, 8/1 and the control without sulfate) through the addition of sodium sulfate, to investigate the effect of sulfate and iron reduction on the reductive dechlorination of pentachlorophenol (PCP). Two sequential incubation periods were carried out with the stage I incubation conducted under a low electron donor concentration (0.5 mM lactate) and stage II incubation conducted under increased electron donor supply with lactate at 20 mM. During stage I, the production of Fe(II) occurred markedly while sulfate reduction and PCP dechlorination rate were low, with the highest dechlorination rates of PCP only 11.0% among all treatments at the end of stage I incubation. During stage II, both PCP dechlorination and sulfate reduction were greatly enhanced in all treatments, while the concentration of Fe(II) changed slightly. The rate of PCP dechlorination decreased (from 87.7% to 34.2%) with the increase of sulfate concentration (from Fe/S mole ratio of 8/1 to 1/3). Our study suggested that the presence of a certain amount of sulfate might facilitate PCP dechlorination in the range of Fe/S mole ratios greater than 1 when compared with the control without SO4 2− . With the investigation of the dechlorination of PCP under the Fe-S-PCP coexisting condition with different Fe/S mole ratios, our study may provide improved strategy for optimizing the remediation of flooded soils and sediments polluted by PCP. Highlights: The Fe-S-PCP coexisting anoxic system was built up with different Fe/S mole ratios. Fe(III) reduction was initiated first and complete during the stage I incubation. Sulfate reduction was enhanced during the stage II incubation. The dechlorination rate of PCP decreased with the increase of sulfate concentration. Our study provides improved strategy for remediation of PCP polluted soils.